2010
DOI: 10.7202/1002175ar
|View full text |Cite
|
Sign up to set email alerts
|

Public and Elite Policy Preferences: Gay Marriage in Canada

Abstract: This paper explores the role of parties, interest groups and public opinion in the enactment of ‘controversial’ social policy particularly when the issue is salient with political elites, but not salient with the public. The author analyses party documents, interest group testimony, media statements and public opinion data. He finds that political elites in Canada facilitated the legalisation of gay marriage while anti-gay marriage politicians and interest groups were unable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Adam cites Canada as an example of union influence on gay marriage. Yet, work on gay marriage politics in Canada does not suggest that unions have had as prominent of a role as Adam seems to suggest (See Larocque 2006;Smith 2008;Rayside 2008;Pettinicchio 2010). Although some scholars have sought to explain the role of unions in promoting equality and diversity (see for instance, Hunt and Rayside 2007), the precise and direct role of labor unions in the national gay marriage policy debate, particularly in a comparative perspective, is underexplored.…”
Section: Sympathetic Allies and Political Elitesmentioning
confidence: 94%
See 1 more Smart Citation
“…Adam cites Canada as an example of union influence on gay marriage. Yet, work on gay marriage politics in Canada does not suggest that unions have had as prominent of a role as Adam seems to suggest (See Larocque 2006;Smith 2008;Rayside 2008;Pettinicchio 2010). Although some scholars have sought to explain the role of unions in promoting equality and diversity (see for instance, Hunt and Rayside 2007), the precise and direct role of labor unions in the national gay marriage policy debate, particularly in a comparative perspective, is underexplored.…”
Section: Sympathetic Allies and Political Elitesmentioning
confidence: 94%
“…In addition, Canadian voters remained uninterested in SSM. For these and other reasons, morality issues like SSM have not historically served as divisive wedge-issues (see Smith 2005a;Rayside 2008;Pettinicchio 2010).…”
Section: Cross-sectional Comparisons Of Political Institutionsmentioning
confidence: 98%
“…Scholars have also shown that elites can take up a cause because of personal histories, career ambitions, or for ideological reasons (Costain and Majstrovic 1994; Reichman and Canan 2003; Sulkin 2005). Thus, if SMOs seek to influence politicians, it is important to know when and how they will be influential particularly if the goals of a movement are not congruent with those of the electorate or with the agenda of political elites (see Burstein and Linton 2002; Pettinicchio 2010). In other words, exploring the role of institutional activists also means understanding how social movement activists and groups work with insiders, or themselves become insiders.…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, the idea of a press bias could have an impact since almost all Canadians would only have access to the Parliamentary debate through the media. Some researchers have studied press coverage in contrast to public opinion polls on the issue o f SSM (Pettinicchio, 2010) to determine if there is a correlation Pettinicchio asked if an issue that is salient in the media is also salient in the public (2012, p. 130) which is yet another approach to considering press agenda. In fact he found the issue was not salient in the public.…”
Section: How Did Newspapers Present the Ssm Debate?mentioning
confidence: 99%
“…One final article explores the idea o f issue salience in the context o f elite and public preferences in Canada Pettinicchio (2010). cites McCombs and Shaw who argue that "the media is likely the only means by which the public, which does not participate in day-to-day politics and therefore is not aware of new political developments, receives information about political events"(2010, p. 130).…”
mentioning
confidence: 99%